1991
DOI: 10.1128/aac.35.8.1661
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of the mec region of an American methicillin-resistant Staphylococcus aureus strain

Abstract: We mapped part of the mec region of a locally prevalent strain of Staphylococcus aureus. The mec region was found to harbor an insert of the transposon Tn554, which encodes spectinomycin and macrolide-lincosamide-streptogramin B resistance, and a 4.6-kb segment of DNA that contains the kanamycin resistance gene aadD. This 4.6-kb segment appears to be an integrated form of a previously described plasmid, pUB110, and is flanked by copies of the insertion sequence IS257. The integration event may be an example of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…The tetA(K) gene and upstream sequence were found to be identical to those of pT181 (13). However, sequencing of the replication region of the cointegrated plasmid revealed that the repC gene contains a 10-bp duplication (corresponding to nucleotides [nt] 4370 to 4379 of pT181 [GenBank entry J01764]) which has resulted in a truncated RepC protein of only 30 amino acids, consistent with the suggestion that the repC gene of the cointegrated pT181 in ANS46 is defective (6). These findings, therefore, confirm the presence of the proposed hybrid promoter upstream of tetA(K) in SK1660, designated P hybrid , consisting of the candidate Ϫ35 and Ϫ10 sequences, TTGCAA and TATATT, respectively, separated by 17 bp (Fig.…”
Section: Resultssupporting
confidence: 54%
“…The tetA(K) gene and upstream sequence were found to be identical to those of pT181 (13). However, sequencing of the replication region of the cointegrated plasmid revealed that the repC gene contains a 10-bp duplication (corresponding to nucleotides [nt] 4370 to 4379 of pT181 [GenBank entry J01764]) which has resulted in a truncated RepC protein of only 30 amino acids, consistent with the suggestion that the repC gene of the cointegrated pT181 in ANS46 is defective (6). These findings, therefore, confirm the presence of the proposed hybrid promoter upstream of tetA(K) in SK1660, designated P hybrid , consisting of the candidate Ϫ35 and Ϫ10 sequences, TTGCAA and TATATT, respectively, separated by 17 bp (Fig.…”
Section: Resultssupporting
confidence: 54%
“…gene was similar to that of MRSA strain ANS46 described previously by Dubin's group (4,6). Taking advantage of this similarity, we could successfully amplify DNA fragments covering the entire SCCmec of 85/2082 by long-range PCR with several sets of primers.…”
mentioning
confidence: 77%
“…IS431 is known to serve as a chromosomal deposit site for multiple resistance genes (21). The integrated copies of pUB110 (in type II SCCmec) and pT181 (in type III SCCmec) were flanked by two copies of IS431 (6,22). Direct repeats were present at both ends of these integrated plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…The ant(4Ј)-I, aac(6Ј)-aph(2Љ), and aph(3Ј)-III genes were evident in 84.5, 61.7, and 8.9% of isolates, respectively. One of the reasons why the ant(4Ј)-I gene is the most frequent is that it adjoins the mecA gene (5,31). In contrast, isolates with coagulase type I, IV, or VII did not carry (Table 2).…”
Section: Discussionmentioning
confidence: 96%